Personal bankruptcy and wage garnishment - Florian Exler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Bankruptcy legislation has important welfare effects on the aggregate economy through effects on prices of and access to credit. Policy makers face a trade-off between insuring individuals against adverse shocks and providing incentives to repay debt. While the U.S. regime has a strong insurance component, many European systems are stricter in that they force delinquent households to repay (parts of) the outstanding debt through wage garnishment. This paper examines labor supply effects of the German garnishment regime and their effect on credit prices. I find that the income cap at 3, 200 EUR net income per month depresses high wage workers labor supply during bankruptcy by about 20%. Three policy experiments are conducted to reduce the burden of income garnishment. In all cases, the amount of credit in the economy declines and default rates drop by 46% to 56%. This comes from a strong increase in credit prices since banks expect lower repayment. It is shown that removing the income cap and lowering garnishment rates significantly reduces adverse labor supply effects. When reducing the garnishment rate from 70% to 30%, disposable income of highly productive households with 60, 000 EUR gross labor income increases by nearly 2/3 under garnishment. On average, the economy would highly profit from abolishing wage garnishment. Removing garnishment would be equivalent to permanently increasing consumption by 1.5% each year. While these gains are quite substantial, young households suffer from restricted access to credit while households in their prime age enjoy better insurance against adverse events.
Keywords: E21; E44; G19; 330